Relasi Kekerabatan Patronase Masyarakat Muna - Asliah Zainal; Muhammad Asrianto Zainal; Waode Ainul Rafiah; Wa Kina Wa Kina (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
This study is addressed to two things: the relationship of kinship and patronage, which take place in social aspect (education and economy) and culture (life cycle ceremony), and the relation of patronage kinship system, which implies on cohesion social community of Muna. This study showed that the relation of the Muna family was tied socially and culturally by two vertices, descent/affinity relation and patronage relation or patronage kinship system and in local term called intaidi bhasitie (we are family). The patronage kinship in Muna family works in almost every aspect of community life, both in social; educational, economic, even political; and cultural (life cycle ceremony). By using Anthropological family, this study argues that the kinship systems wrapped by patronage or boosted patronage by kinship relationships are neither firm nor sustainable. It may be safe in education, economy, and cultural aspects but may be weakened in political preference. Even though a relative still tied up in a family's node but his indifference will be called "family but not". This social relationship will threaten the bond of kinship that eventually fragile and unravel, and the social relation seems to be a pseudo kingship. This research implies that the social relations of patronage kinship will threaten kinship ties which are eventually fragile and unravel, resulting in pseudo kingship if the conditions for a patron-client as Scott's theory are not fulfilled, and eventually become a transactional relationship bond. This research is expected to provide an understanding that kinship ties or patronage relations are traditionally socio-cultural capital that is increasingly threatened by the demands of economic and political interests in modern transactional relationships.